“MISS CLINIC” AI CHATBOT ASSISTANT FOR ANSWERING QUESTIONS AND INQUIRIES OF MEDICAL FACILITY OPERATORS IN NAKHON PATHOM PROVINCE - Pamonsinlapatham, Koomkwan (Thai Bulletin of Pharmaceutical Sciences, 2026)
Private medical facility that do not provide in-patient service, or private clinics, in Nakhon-Pathom province are required to obtain a license from the consumer protection and public health pharmacy division, provincial Public Health Office (PHO), in accordance with the Healthcare Facilities Act B.E. 2541 (1998) and its amendments. They also need information regarding the licensing process and require immediate responses. “Miss Clinic” was developed as an assistant to answer important questions, compiled from questions previously received from healthcare providers and staff at the Nakhon-Pathom PHO, as well as problems encountered during the licensing process. It was developed using the LINE application, incorporating dialogue flow and Google AppScript, with Google Sheets as its database. Furthermore, it integrates with the information systems of the Nakhon Pathom PHO provide a service that answers the questions of entrepreneurs such as the licensing process inquiry system, the system for compiling licensing application documents, and the application status tracking system. The study showed that "Miss Clinic" develop and implement with over 100 entrepreneurs participating in testing (On January 2024). From 90 respondents who evaluated the questionnaire during Febuary - April 2024, the chatbot’s ability to provide up-to-date information (4.67±0.47), answer questions correctly (4.61±0.49), and answer questions quickly (4.68±0.47) is at the highest level. Satisfaction with the service in all aspects is at a high level. "Miss Clinic" was successfully developed according to its objectives and has been directly used with entrepreneurs, providing accurate and relevant information, resulting in high satisfaction with the service. There is also the potential to expand the service to answer questions related to consumer protection and public health pharmacy in other areas such as food, drugs, and cosmetics, etc.